Implementasi Pendistribusian Dana Zakat Infaq Dan Shadaqah (ZIS) Pada Bidang Pendidikan Untuk Pemberdayaan Pendidikan Di BAZNAS Sidoarjo - Arafat, Syihabuddin; Fahrullah (Universitas Negeri Surabaya, 2019)
Implementing the zakat is obligatory for all Muslims. With it the weak communities zakat can get welfare in terms of the material or spiritual. The function of education is very important for humans because it not only educate the nation but also improve quality of life. BAZNAS Sidoarjo discerning programs have Sidoarjo Smart program has disbursed grants zakat to education with the goal of keeping the public education assistance fund Sidoarjo over her son who are continuing their education. This research uses qualitative descriptive method. The purpose of this research was to learn the system of tithes on education distribution of funds. From the results of the research can be concluded distribution ZIS on education already optimal, only understanding of the people about the education assistance is still lacking.